On the types of Maxillaria grandiflora and Heterotaxis valenzuelana (Orchidaceae: Maxillariinae) - Blanco Coto, Mario Alberto (2011)
The type specimen of Maxillaria grandiflora (Kunth) Lindl. was collected by Alexander von Humboldt and Aimé Bonpland during their scientific expedition to Tropical America. Its type locality, which has been the subject of confusion, is identified as a place on the eastern part of La Cruz municipality in the province of Nariño, Colombia. The type of M. grandiflora is shown to be a mixed collection and a lectotype is designated; the protologue illustration represents an amalgamation of both species. The type of Heterotaxis valenzuelana (A. Rich.) Ojeda & Carnevali was collected by José María Valenzuela but has been erroneously cited as Wright 3314 in the recent literature.